Characterization of the vitrification parameters for oviduct aggregates in Camelus dromedarius - El-Sokary, Mohamed M. M.; Albreiki, Hamad A.; Shehata, Seham F.; Mahmoud, Karima Gh. M. (Frontiers in Veterinary Science, 2025)
IntroductionCamel oviductal isthmus aggregates provide a novel and promising model for studying sperm attachment and longevity, offering a potential alternative for short-to mid-term sperm preservation and transport under non-cryogenic conditions. Effective cryopreservation of the aggregates for later use can contribute to addressing challenges associated with camel semen preservation by potentially extending sperm lifespan and facilitating semen transport to remote areas without cryogenic facilities. Challenges in preserving the structural integrity and viability of camel oviductal aggregates remain a key critical gap during cryopreservation. This study evaluated the efficiency of vitrification protocols for camel oviductal isthmus aggregates, focusing on the effects of aggregate size, cryoprotectants (CPA), cryodevices, post-thaw viability, and sperm-binding capacity.MethodsAggregates retrieved from the oviductal isthmus were classified into four size groups (50, 100, 150, and 200 μm) and vitrified to determine the influence of size on post-thaw outcomes. CPA concentrations (3, 5, and 7 M) of DMSO and EG in a 1:1 ratio were tested for their impact on structural integrity and viability. The performance of cryodevices, including cryovials, 0.5 mL straws, and 0.25 mL straws, was also assessed.Results and discussionThe results indicated that aggregates sized 150 μm and 200 μm demonstrated superior post-thaw viability, with intactness rates of 78 ± 2.0% and 83 ± 2.8%, respectively. Among the tested CPA concentrations, 7 M showed the highest post-vitrification viability (69 ± 1.9%). Additionally, 0.25 mL straw cryodevice achieved significantly better post-thaw viability (67 ± 2.7%) compared to 0.5 mL straws (32 ± 2.1%) and cryovials (10 ± 1.1%). Regarding sperm-binding capacity post-thaw, aggregates treated with 5 M (69 sperm) and 7 M (74) CPAs showed the highest binding rates, with no significant difference between these concentrations. Further studies are required to optimize vitrification protocols to enhance the aggregate’s post-vitrification viability and structural integrity.